PENGARUH NON-DEBT TAX SHIELD, FINANCIAL DISTRESS, DAN KINERJA KEUANGAN TERHADAP MANAJEMEN LABA - HELISSE ARTEJA; AAN MARLINAH; DICKY SUPRIATNA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Financial statements are used to demonstrate the effectiveness of achieving company goals and serve as a basis for decision-making by shareholders. Profit information, as a key performance indicator, is often manipulated through earnings management practices to influence shareholder perceptions. This study empirically examines the impact of non-debt tax shields, financial distress, profitability, operating cash flow, firm size, firm growth, managerial ownership, and board size on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The sample was selected using purposive sampling, consisting of 52 companies and 156 observations, analyzed using multiple linear regression. The results show that financial performance, namely profitability and firm growth have a positive effect on earnings management, while operating cash flow has a negative effect. Other variables do not have an impact on earnings management.